2019
DOI: 10.7554/elife.41431
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomic atlas of HIV infection in primary human CD4+ T cells

Abstract: Viruses manipulate host cells to enhance their replication, and the identification of cellular factors targeted by viruses has led to key insights into both viral pathogenesis and cell biology. In this study, we develop an HIV reporter virus (HIV-AFMACS) displaying a streptavidin-binding affinity tag at the surface of infected cells, allowing facile one-step selection with streptavidin-conjugated magnetic beads. We use this system to obtain pure populations of HIV-infected primary human CD4+ T cells for detail… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 105 publications
2
56
0
Order By: Relevance
“…C -Classical monocyte sample, I -Intermediate monocyte sample, NC -Non-classical monocyte sample. (2020) 10:4560 | https://doi.org/10.1038/s41598-020-61356-w www.nature.com/scientificreports www.nature.com/scientificreports/ other cell surface proteomic analyses in primary cells have been limited to CD4+ T-cells 16 , erythrocytes 17,18 , NK cells, adipocytes and a subset of tumour cells 19 . We quantify 373 cell surface proteins from classical monocytes, and further quantify 313 proteins across all monocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…C -Classical monocyte sample, I -Intermediate monocyte sample, NC -Non-classical monocyte sample. (2020) 10:4560 | https://doi.org/10.1038/s41598-020-61356-w www.nature.com/scientificreports www.nature.com/scientificreports/ other cell surface proteomic analyses in primary cells have been limited to CD4+ T-cells 16 , erythrocytes 17,18 , NK cells, adipocytes and a subset of tumour cells 19 . We quantify 373 cell surface proteins from classical monocytes, and further quantify 313 proteins across all monocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the first cell surface proteomic study in primary monocyte subsets. Up to now, other cell surface proteomic analyses in primary cells have been limited to CD4+ T-cells 16 , erythrocytes 17,18 , NK cells, adipocytes and a subset of tumour cells 19 . We quantify 373 cell surface proteins from classical monocytes, and further quantify 313 proteins across all monocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Vpr/Vif-mediated G2/M arrest studies have been performed in cycling cells including T cell lines [107,109,111,113,121,122], THP-1 [99], Hela and HEK293 [98,113,122], and primary CD4 T cells [120,123].…”
Section: What Is the Role Of Vpr/vif-mediated G2/m Arrest In Terminalmentioning
confidence: 99%
“…Indeed the Vif-dependent depletion of PPP2R5A causes an increase in protein phosphorylation in HIV-infected cells, including that of substrates of the aurora kinases and CDK1 [ 114 ]. It has been concluded that the depletion of the PPP2R5 family subunits is necessary for Vif-dependent cell cycle arrest [ 101 , 113 , 119 , 120 ].…”
Section: Hiv-1 Regulates the Host Cell Cyclementioning
confidence: 99%